Adjuvant chemotherapy in pancreatic cancer: state of the art and future perspectives. Issue 4 (July 2020) - Mas, Léo; Schwarz, Lilian; Bachet, Jean-Baptiste
Abstract : Purpose of review: The modalities of management of resectable pancreatic ductal adenocarcinoma (PDAC) have evolved in recent years with new practice guidelines on adjuvant chemotherapy and results of randomized phase III trials. The aim of this review is to describe the state of the art in this setting and to highlight future possible perspectives. Recent findings: Resectable PDAC is the tumor without vascular contact or a limited venous contact without vein irregularity. Several pathologic and biologic robust prognostic factors such as an R0 resection defined by a margin at least 1 mm have been validated. In phase III trials, the doublet gemcitabine-capecitabine provided a statistically significant, albeit modest overall survival benefit, but failed to show an improvement in relapse-free survival. Similarly, gemcitabine plus nab-paclitaxel did not increase disease-free survival. Modified FOLFIRINOX led to improved disease-free survival, overall survival, and metastasis-free survival, with acceptable toxicity. In the future, prognostic and/or predictive biomarkers could lead the optimization of therapeutic strategies and neoadjuvant treatment could become a standard of care in PDAC. Summary: After curative intent resection, modified FOLFIRINOX is the standard of care in adjuvant in fit patients with PDAC. Others regimens (monotherapy or gemcitabine-based) are an option in unfit patients.